Predictive Brain Signals of Linguistic Development - Kooijman, Valesca; Junge, Caroline; Johnson, Elizabeth K.; Hagoort, Peter; Cutler, Anne (Frontiers in Psychology, 2013)
The ability to extract word forms from continuous speech is a prerequisite for constructing a vocabulary and emerges in the first year of life. Electrophysiological (ERP) studies of speech segmentation by nine- to 12-month-old listeners in several languages have found a left-localized negativity linked to word onset as a marker of word detection. We report an ERP study showing significant evidence of speech segmentation in Dutch-learning seven-month-olds. In contrast to the left-localized negative effect reported with older infants, the observed overall mean effect had a positive polarity. Inspection of individual results revealed two participant sub-groups: a majority showing a positive-going response, and a minority showing the left negativity observed in older age groups. We retested participants at age three, on vocabulary comprehension and word and sentence production. On every test, children who at seven months had shown the negativity associated with segmentation of words from speech outperformed those who had produced positive-going brain responses to the same input. The earlier that infants show the left-localized brain responses typically indicating detection of words in speech, the better their early childhood language skills.